The Communicative Approach Enhancing Speaking Skill: Implementation in the Matriculation Class of Darussalam Gontor University - Gautama Veri Vetiana; Umi Machmudah; Dewi Chamidah; Moh. Buny Andaru Bahy; Bakri Muhammad Bakheet; Umma Fatayati (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Background: Arabic learning at Islamic Religious Colleges focuses on speaking proficiency, but matriculation students often face obstacles when adapting. To overcome this, communicative methods are needed that emphasize active interaction and practical language practice, both in the classroom and in the dormitory. Research Objectives: This study aims to reveal the effectiveness of applying communicative methods in improving Arabic speaking skills among matriculation class students at Darussalam Gontor University. Methodology: This research employs a qualitative approach with a case study design. Data were collected through observation and semi-structured interviews. Informants were selected purposively and consisted of the language development directorate, lecturers, tutors, students, and dormitory managers. The data were analyzed systematically to understand the implementation process and its impact on students’ speaking abilities. Results: The findings indicate that the application of communicative methods improves students’ Arabic speaking skills and encourages active participation throughout the learning process. Students become more confident in using Arabic in classroom interaction and daily communication. Supporting elements such as the language environment, daily vocabulary programs, and learning motivation strengthen the effectiveness of the method. However, several challenges appear, particularly the heterogeneous educational backgrounds of students which influence their initial language proficiency. Unique Contribution: This study provides empirical insight into how communicative methods function in an intensive language environment that integrates classroom learning with dormitory-based language practice. The research highlights the role of institutional language policies and daily vocabulary programs in supporting communicative language learning. Conclusion: The study confirms that a consistently implemented communicative approach can increase students’ confidence and improve Arabic speaking skills naturally. Continuous interaction and contextual language use play a central role in developing students’ oral proficiency. Recommendations: Educational institutions should design Arabic language curricula that integrate communicative learning strategies with a structured language environment. Institutions should also provide consistent speaking practice, vocabulary enrichment programs, and motivational support to accommodate students with diverse educational backgrounds.